The chronotype conjecture in the association between dietary carbohydrate intake and high-sensitivity C-reactive protein (hs-CRP): a cross-sectional study from NHANES 2015 data - Ngo-Nkondjock, Raissa Victorine; Yuntao, Zhang; Adnan, Humara; Adnan, Sheikh Muhammad; Cheteu, Thérèse Martin Wabo; Li, Ying (Sleep Science, 2021)
Substantial evidence suggests that the timing of macronutrient intake affects cardiovascular health. The present study aims to assess the association between the dietary carbohydrate intake (DCI) and the high-sensitivity C-reactive protein (hs-CRP) combined with the implication of the chronotype. Thus, we explored the most recently released National Health and Nutrition Examination Survey (NHANES) data. We analysed data from 5,616 participants of the NHANES in 2015. We selected participants with available data for the DCI, sleep and wake-up time, and the hs-CRP. Chronotypes were categorized according to the sleep times. Binary logistic regression analysis was performed to predict participants with low or high levels of hs-CRP based on the DCI and chronotypes. Moderation analysis was used to investigate the effect of the chronotypes on the DCI-hs-CRP’s association. A higher DCI was significantly associated with the higher hs-CRP levels (odds ratio (OR) = 1.36, 95% confidence interval (CI) = [0.9-1.8]). Moderate evening (ME) chronotypes had higher risk for high hs-CRP level (OR = 1.15, 95% CI = [1.22-1.23]) compared to the intermediate and the morning chronotypes. The chronotype significantly moderated the hs-CRP given the DCI (moderation coefficient, α2=0.05, 95% CI = [0.01-0.08]). The chronotype diminished the hs-CRP predicted by the DCI. The findings of the study underscore the significance of assessing the protective effect of individuals’ chronotype concerning cardiovascular health.
Keywords: Carbohydrates Intake; Cardiovascular Health; Dietary Carbohydrates; Cardiovascular Diseases; Ethnicity and Health